Faktor-Faktor yang Mempengaruhi Pendapatan Pengrajin Anyaman Lontar di Desa Aeramo Kecamatan Aesesa Kabupaten Nagekeo - Marques, Margaretha T. B.; Luciany, Yohanes Paulus; Djata, Baltasar Taruma (JURNAL EQUILIBRIUM, 2024)
This study aims to determine the effect of capital, labor, work experience and education on the income of palm woven craftsmen in Aeramo Village, Aesesa District, Nagekeo Regency through data sourced from palm woven craftsmen with calculations using the SPSS Program. The analysis technique used is multiple linear regression. To calculate the multiple linear regression equation, the data must meet the basic assumption test, namely through hypothesis testing. The coefficient value of the capital variable is 0.521 with tcount table (4.866 > 2.048), the coefficient value of the labor variable is 0.404 with tcount > table (4.061 > 2.048), the coefficient value of the work experience variable is 0.224 with tcount > ttable (2.891 > 2.048) and education variable coefficient value is 0.362 with tcount > ttable (2.715 > 2.048). Then for the F test, the value of Fcount Ftable (11.348 2.99).